Enforcing architectural contracts in high-level synthesis - Patil, Nikhil; Bansal, Ankit; Chiou, Derek (2011 48th ACM/EDAC/IEEE Design Automation Conference (DAC), 2011)
We present a high-level synthesis technique that takes as input two orthogonal descriptions: (a) a behavioral architectural contract between the implementation and the user, and (b) a microarchitecture on which the architectural contract can be implemented. We describe a prototype compiler that generates control required to enforce the contract, and thus, synthesizes the pair of descriptions to hardware.